Model Minat Beli dengan Mediasi Sikap Merek Melalui Penempatan Produk dan Celebrity Endorser - Sadewi, Ade Windu; Herman, Herman; Hambalah, Febrina (Jurnal Ilmu Manajemen dan Bisnis, 2023)
Companies in the modern era are required to carry out all strategies to maintain their products with the aim of meeting consumer needs. Fast Moving Consumer Goods (FMCG) industry is an industry that moves to meet daily needs ranging from the food, beverage, household needs and body care sectors. The food sector, especially confectionery, generates sales of around US$ 10 Billion annually. One company that has succeeded in exporting its products to foreign countries is PT. Mayora Indah, Tbk with Kopiko which is in demand in various countries. Kopiko in 2021 advertised its products in the Korean drama Vincenzo with Song Joong-ki as the main character. This study aims to determine the effect of product placement and celebrity endorser on purchase intention with brand attitude as a mediator. The method used is quantitative associative explanation. The study was conducted on 130 Surabaya residents who watched the drama Vincenzo with a sample size guideline according to Hair et al. (2017). Data collection techniques using a questionnaire and data analysis Structural Equational Modeling (SEM) with the analysis tool SmartPLS 3.2.9 full version. The results of this study indicate that celebrity endorsers have no significant effect on purchase intention and need mediation from brand attitudes to have a significant effect; product placement has a significant effect on purchase intention with and without brand attitude as a mediator; and brand attitudes have a significant effect on audience purchase intention.